Trench, lollipop, lift and chop technique for mild to moderate cataracts - Vivekanand, U; Kulkarni, C (Nepalese Journal of Ophthalmology, 2012)
No abstract available.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6561 Nepal J Ophthalmol 2012; 4 (2): 344-345